OPTIMALISASI DESTINASI WISATA KALIMAS MELALUI PENGEMBANGAN FASILITAS PUJASERA - Truli Nugroho; Andreas Aris Eko Mulyono; Suryo Adinugroho; Kristian Faskahariyanto; Jeremy Teira Taosu; Anjelino Da Silva (POLITEKNIK LP3I JAKARTA, 2025)
The Kalimas River tourist destination in Surabaya has great potential to be developed as a leading tourist destination in Surabaya. This research aims to identify the role of developing food court facilities in optimizing the Kalimas River tourist destination in Surabaya. The research method used is a mixed method with a qualitative and quantitative approach. The research results show that the development of food court facilities contributes significantly to increasing tourist attraction, visitor satisfaction and regional income. With adequate food court facilities, tourists can enjoy a variety of typical culinary choices that support a more complete and satisfying tourism experience. This research is an in-depth analysis of the influence of food court facilities on river tourism destinations, which has not been widely studied in Indonesia. The aim of this research is to test the potential for the development of Pujasera as a strategy to optimize tourism destinations on the Kalimas River in Surabaya. The research results show that well-integrated food facilities will improve tourist attractions, extend the length of tours, and promote the economy of the surrounding community. These findings are expected to be a reference for tourism destination producers and political-manager decisions in facility design that supports tourism sustainability.